Developmental stability of foraging behavior: evaluating suitability of captive giant pandas for translocation - Swaisgood, R. R.; Martin‐Wintle, M. S.; Owen, M. A.; Zhou, X.; Zhang, H. (Animal conservation, 2018)
The behavioral competence of captive‐bred individuals – an important source population for translocation programs – may differ from that of wild‐born individuals and these differences may influence post‐release survival. Some behaviors will be more robust, or developmentally stable, than others in the face of the environmental novelties of captivity. Here, we investigated developmental stability of foraging behavior by quantifying bamboo feeding behavior in captive‐bred and wild‐born giant pandas, Ailuropoda melanleuca. As an energy‐limited species adapted to a low‐nutrition diet, any reductions in feeding efficiency may compromise post‐release survival. Using video of 22 captive pandas, we measured several components of the panda's elaborate bamboo feeding behavior repertoire. We found that captive‐born and wild‐born pandas displayed the same repertoire of feeding behaviors, suggesting developmental stability in these motor patterns, but that they employed them differently with different parts of the bamboo. Captive‐born pandas devoted less time and effort to handling and chewing leaves while allocating more effort to the consumption of large culms than did wild‐born pandas. Captive‐born pandas also handled small culm and stripped small culms to prepare them for consumption less often than did wild‐born pandas. All of these behavioral differences indicate that wild‐born pandas in captivity behave in a manner more similar to wild pandas, and focus their behavioral effort on more nutritious bamboo. Thus, these aspects of captive‐born panda feeding behavior may be compromised, and were not developmentally stable in the captive environment. These behavioral differences are cause for concern and should be the subject of future study to determine whether they forecast compromised fitness in translocations. Evaluating developmental stability and behavioral competence should be a key component of captive‐release translocation programs, serving to guide pre‐release training and selection of individuals to be released. The behavioral competence of captive‐bred individuals may differ from that of wild‐born individuals and these differences may influence post‐release survival in translocation programs. We investigated developmental stability of foraging behavior by quantifying bamboo‐feeding behavior in captive‐bred and wild‐born giant pandas. Wild‐born pandas in captivity behaved in a manner more similar to wild pandas, and focused their behavioral effort on more nutritious bamboo, indicating that captive‐born panda feeding behavior may be compromised and that feeding behavior is influenced by development in a captive environment.